Female reproductive organs tissue engineering - Liverani, Liliana; Bleisinger, Nathalie; Beckmann, Matthias; Dittrich, Ralf (Elsevier, 2021)
The present chapter is focused on the tissue engineering approach applied to female reproductive organs. This field was quite often presented as urogenital applications, but recently the interest of the scientific community has been more oriented on the reproductive organs and to the evaluation of tissue engineering-based approaches focusing on the selection of biomaterials and scaffold fabrication technologies to develop suitable biomimetic three-dimensional constructs.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Biomaterials; Fallopian tubes; Ovary; Reproductive organs; REPROTEN; Tissue engineering; Uterus